Simulation of functional restrictions in swimmers with disabilities - Schega, L.; Kunze, K.; Daly, D. (First international symposium sciences and practices in swimming, 2006)
A fair System of classification is fundamental to organising sport competition for swimmers with loco-motor disabilities. Nevertheless, continuing assessment of the fairness of the existing System is needed. In this study functional impairments (amputations vs. paralysis) were simulated with a human model commonly used in crash tests. The passive drag in water (FPD) was registered during a towing trail with the "Portable Swim specific Test and Training device (PSTT)". The results were compared with values of athletes with loco-motor disabilities. The Simulation results obtained for amputations are not valid. In contrast, results for persons with paralysis could conceivable be obtained from crash dummy tests. The simulations are valid for only one of the groups tested, far-reaching recommendations regarding the Functional Classification System cannot yet be made and further testing still needs to be done on real skilled athletes with disabilities.